Analyzing nonlocal effects in the plasmon spectra of a metal slab by the Green’s function technique for hydrodynamic model - Kang, Naijing; Miškovic, Z.L.; Zhang, Ying-Ying; Song, Yuan-Hong; Wang, You-Nian (Nanoscale systems mathematical modeling, theory and applications, 2014)
We study the dynamic response of a metal slab containing electron gas described by the hydrodynamic model with dispersion. The resulting wave equation for the perturbed electron density is solved by means of the Green’s function that satisfies Neumann boundary conditions at the endpoints of the slab. This solution is coupled with the electrostatic potential, which is expressed in terms of the Green’s function for the Poisson equation for a layered structure consisting of three dielectric regions. As an illustration, a set of dispersion relations for eigenfrequencies is deduced for the plasma oscillations in the electron gas, corresponding to both the surface and the bulk modes of even and odd symmetry with respect to the center of the metal slab.